Eating disorders in female athletes: a review of prevalence and pathogenic behaviors - Toni M. Torres-McGehee; Nancy A. Uriegas; Carli Mendelow; Alexis Soucy (Lesya Ukrainka Volyn National University, 2024)
Relevance of Research Topic. Eating disorders can be a result of multiple factors including disordered eating, which is an array of abnormal eating behaviors including restrictive eating, fasting, frequently skipped meals, diet pills, overeating, binge-eating and then purging (vomiting). The athletic and performing art populations, specifically females, are at high risk of eating disordered compared to non-athletes and may be predisposed further depending on the nature of their sports. Purpose. The intention of this review article is to identify and review the types of feeding and eating disorders, pathogenic behaviors, prevalence of eating disorders, and risk factors for eating disorders in female athletes. Results. The review of the literature revealed that female athletes are at risk for eating disorders and pathogenic behavior engagement. Conclusions. As more information is provided to the public regarding the determinants and distribution of factors present in potentially at-risk females to developing an eating disorder, more awareness is made to continue the research and promotion of treatment. Appropriate interventions should follow best practices, incorporating a multidisciplinary care team, including a physician, dietitian, mental health professional, and athletic trainer.